Violence Against Husbands in Domestic Life - Ferian Adam; Hanafi Arief; Muhammad Aini (Journal of Social Research, 2025)
Domestic violence is a topic that has recently been discussed extensively, from ordinary people to public figures, becoming a trending topic on social media and national television. Victims of domestic violence are also experienced by husbands, with forms of violence that can be physical or psychological. However, the laws that have been formed are often understood by the general public as only providing legal protection to wives who are victims of domestic violence, leading to misunderstandings regarding husbands' rights to legal protection. This research aims to determine the regulation and protection of husbands who experience domestic violence. This research employs normative legal research methodology, using statutory and conceptual approaches. The legal materials consist of primary and secondary sources, analyzed through various legislative sources and legal expert references. The research results indicate that legal arrangements for wives who commit domestic violence against husbands according to Law Number 23 of 2004 concerning the Elimination of Domestic Violence consist of two forms: (1) prison sentences and fines, specifically regulated in Articles 44 to 49, with Article 44 specifically addressing physical violence; and (2) additional punishment, which shows that the form of punishment for perpetrators of domestic violence in positive law is regulated in separate regulations outside the Criminal Code.